Proteomic profiling spotlights the molecular targets and the impact of the natural antivirulent umbelliferone on stress response, virulence factors, and the quorum sensing network of Pseudomonas aeruginosa - Kasthuri, Thirupathi; Barath, Sivaraj; Nandhakumar, Muruganandam; Karutha Pandian, Shunmugiah (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas aeruginosa easily adapts to newer environments and acquires several genome flexibilities to overcome the effect of antibiotics during therapeutics, especially in cystic fibrosis patients. During adaptation to the host system, the bacteria employ various tactics including virulence factor production and biofilm formation to escape from the host immune system and resist antibiotics. Hence, identifying alternative strategies to combat recalcitrant pathogens is imperative for the successful elimination of drug-resistant microbes. In this context, this study portrays the anti-virulence efficacy of umbelliferone (UMB) against P. aeruginosa. UMB (7-hydroxy coumarin) is pervasively found among the plant family of Umbelliferae and Asteraceae. The UMB impeded biofilm formation in the P. aeruginosa reference strain and clinical isolates on polystyrene and glass surfaces at the concentration of 125 µg/ml. Global proteomic analysis of UMB-treated cells revealed the downregulation of major virulence-associated proteins such as RhlR, LasA, AlgL, FliD, Tpx, HtpG, KatA, FusA1, Tsf, PhzM, PhzB2, CarB, DctP, MtnA, and MscL. A functional interaction study, gene ontology, and KEGG pathway analysis revealed that UMB could modulate the global regulators, enzymes, co-factors, and transcription factors related to quorum sensing (QS), stress tolerance, siderophore production, motility, and microcolony formation. In vitro biochemical assays further affirmed the anti-virulence efficacy of UMB by reducing pyocyanin, protease, elastase, and catalase production in various strains of P. aeruginosa. Besides the antibiofilm activity, UMB-treated cells exhibited enhanced antibiotic susceptibility to various antibiotics including amikacin, kanamycin, tobramycin, ciprofloxacin, and cefotaxime. Furthermore, in vitro cytotoxicity analysis revealed the biocompatibility of UMB, and the IC50 value was determined to be 249.85 µg/ml on the HepG2 cell line. Altogether, the study substantiates the anti-virulence efficacy of UMB against P. aeruginosa, and the proteomic analysis reveals the differential expression of the regulators related to QS, stress response, and motility factors.